Identification of bacterial pathogens from clinical samples using 16S rRNA sequencing - Nguyen, Hoang Bach; Mai, Thi Thao Nhi; Ung, Thi Thuy; Nguyen, Thi Khanh Linh (Tạp chí Y Dược Huế, 2022)
Introduction: Bacterial infections have a substantial impact on global health and can become serious if misdiagnosed with several diseases related to the central nervous, cardiovascular, and respiratory systems. The prognosis in patients with infectious disease strongly depends on early diagnosis and appropriate antibiotic therapy. We aimed to compare the accuracy of genus and species-level identification bacteria using biochemical testing and 16S rRNA sequence analysis. Material and methods: 50 clinical samples were isolated and identified the pathogenic bacteria by routine laboratory methods. In parallel, DNA was extracted from isolate’s colonies and amplified the 16S rRNA gene by using specific primers. The PCR products were evaluated by agarose gel electrophoresis and direct sequencing by the Sanger method. The sequence data were manipulated by Geneious Prime software. The sequence data matching the Prokaryotic 16S Ribosomal RNA database with a similarity score of ≥ 98% were selected. Results: Total of 50 clinical samples were isolated and identified the pathogenic bacteria with common biochemical test and API® Microbial Identification. The sequencing data showed that almost species identified by 16S rRNA sequencing matched the biochemical test method. There are 3 species (6%) were identified as different species with the routine methods. Conclusions: 16S rRNA gene sequencing is more sensitive, easier to manage, more accurate and especially for bacteria that are difficult to identify. 16S rRNA sequencing is considered an effective method to early identify pathogens in clinical samples, and this technique is increasingly being used in microbiology laboratories.